Association of Mesoscale Auroral Structures and Breakups With Energetic Particle Injections at Geosynchronous Orbit - Henderson , M. G. (Frontiers in Astronomy and Space Sciences, 2022)
Geomagnetic substorms are associated with characteristic energetic particle injection signatures at geosynchronous orbit that are often dispersionless in both electrons and ions near the Magnetic Local Time sector of auroral onset locations and are dispersed farther away from this region. Although the precise mechanism responsible for the coherent injection signatures at geosynchronous orbit have been the topic on considerable ongoing debate for decades, recent work on Bursty Bulk Flows (BBFs) in the tail have led to the hypothesis that they may be the result of multiple, overlapping flow bursts penetrating into the inner magnetosphere from more distant downtail reconnection sites. Since auroral streamers are thought to be ionospheric signatures of BBFs in the tail, they can be used as proxies for testing this hypothesis. Using high resolution auroral imagery from the POLAR/VIS instrument combined with multi-spacecraft observations of energetic particle injections at geosynchronous orbit, we examine the association of meso-scale auroral structures with particle injection signatures over many hours during the 9 November 1998 storm. We find that the explosive types of auroral activations, such as pseudo-breakups and substorm onset breakups are associated with the more intense and well-defined dispersed injection signatures, while intervals of isolated streamer activity appear to be associated with smaller dispersed `injectionlet' signatures. Furthermore, intervals of sustained, intense, late expansion phase/recovery phase streamer activity appear to be associated with sustained elevated dispersed particle fluxes. These results are consistent with the hypothesis that it is the overlapping effects of sustained, intense multiple flow bursts penetrating toward the Earth that result in classical substorm particle injection signatures at geosynchronous orbit. However, It is also suggested that torches/omega-band tongues are the prime fate of braking isolated flow bursts (streamers) rather than the development of breakups, bulges and substorm current wedge formation. A statistical analysis is presented showing that: 93% of the observed torches evolved from streamers; 93% of streamers arriving in the equatorward regions of the bulge led to torches; 10.5% of such streamers led to breakups (either pseudo-breakups or substorm onsets); and only 3.5% of such streamers led to substorm onsets.